2023
DOI: 10.1002/csc2.21028
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied aerial systems imagery for phenotyping in cotton, maize, soybean, and wheat breeding

Abstract: High‐throughput phenotyping (HTP) with unoccupied aerial systems (UAS), consisting of unoccupied aerial vehicles (UAV; or drones) and sensor(s), is an increasingly promising tool for plant breeders and researchers. Enthusiasm and opportunities from this technology for plant breeding are similar to the emergence of genomic tools ∼30 years ago, and genomic selection more recently. Unlike genomic tools, HTP provides a variety of strategies in implementation and utilization that generate big data on the dynamic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 255 publications
(308 reference statements)
0
16
0
Order By: Relevance
“…Unlike in precision agriculture studies, we masked the soil in calculating NGRDI so that it is not confounded with plant biomass or canopy coverage. Integrating temporal field‐based high‐throughput phenotyping with temporal modeling approaches such as FPCA, Gaussian peak models, and mechanistic growth models, combined with the association of temporal phenotypes in genetic mapping can unravel the complex intricacies of plant development (Guo et al ., 2021; Herr et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in precision agriculture studies, we masked the soil in calculating NGRDI so that it is not confounded with plant biomass or canopy coverage. Integrating temporal field‐based high‐throughput phenotyping with temporal modeling approaches such as FPCA, Gaussian peak models, and mechanistic growth models, combined with the association of temporal phenotypes in genetic mapping can unravel the complex intricacies of plant development (Guo et al ., 2021; Herr et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Field‐based high‐throughput phenotyping (FHTP) combines cutting‐edge remote sensing technologies with traditional breeding and genetics approaches to rapidly and non‐invasively assess and quantify a wide range of plant traits in natural field conditions (Araus & Cairns, 2014). Field‐based high‐throughput phenotyping has gained significant attention and prominence in recent years due to its potential to accelerate crop improvement and enhance our understanding of plant responses to various environmental stresses (Pauli et al ., 2016; Shi et al ., 2016; Araus et al ., 2018; Wang et al ., 2019, 2021; Anderson et al ., 2020; Zhou et al ., 2021; Adak et al ., 2021a,b, 2023b; Oehme et al ., 2022; Sun et al ., 2022; Herr et al ., 2023; Li et al ., 2023). Field‐based high‐throughput phenotyping involves the integration of advanced sensing technologies, robotics, data analytics, and remote sensing with traditional agronomic practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vegetation index used depends on the crop, growth stage, and target trait. These factors influence reflectance values and relative index effectiveness ( Wientjes et al., 2017 ; Lozada et al., 2020 ; Herr et al., 2023 ). Vegetation indices have many applications in capturing routine trait estimates like plot quality, biotic, and abiotic stress ( Sankaran et al., 2015a ; Guo et al., 2021 ; Sarkar et al., 2022 ; Sapkota et al., 2023 ), as well as previously infeasible traits like chlorophyll content and nitrogen content ( Xie and Yang, 2020 ; Yin et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that SRI data can be utilized to improve tools like genomic selection for grain yield. Thus, grain yield is an appealing trait for a breeder to focus on when implementing HTP approaches ( Reynolds et al., 2020 ; Montesinos López et al., 2022 ; Herr et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%